PERANAN BIOTEKNOLOGI DALAM MENGATASI MULTIKRISIS - Rina Hidayati Pratiwi (Faktor Exacta, 2010)
Economic crisis which knocked over Indonesia in 1998, nowadays have turned into crisis of multidimensional or multicrisis as its effect. In all of aspect, and natural environments even also its impact from effect of careless human being. Indonesia notorious have many natural resources but do not make balance with management effort up at benefit. In fact, this management can be done creatively by using methods of Biotechnology which in fact human being have done since ahead, but only unheard-off. The aim of this writing is to give global Biotechnology information which expected can be exploited creatively by society in managing Indonesia natural resources to our importance. Activity of Biotechnology include transgenic engineering that able to yield better and more product from source of which a little and less potential. For example like agriculture aspect, can increase the yield as well as by using methods of Biotechnology. Until in this time, agriculture have hundreds of gene from various carried over by a success source of crop and produce hundreds of variety type the new crop that called crop of transgenic. With technology of DNA recombinant, modified foreign gene of best variety can be injected to most of all life cells. Keywords: multicrisis, management effort, natural resources, Biotechnology, DNA recombinant